Global Plant and Pest Information System - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Global Plant and Pest Information System GPPIS is a global implementation and extension of the Pacific Plant Protection Information System (PPPIS) developed by the FAO and the South Pacific Commission (SPC)